YAP and TAZ in Vascular Smooth Muscle Confer Protection Against Hypertensive Vasculopathy. Issue 4 (24th February 2022) - Daoud, Fatima; Arévalo Martinez, Marycarmen; Holmberg, Johan; Alajbegovic, Azra; Ali, Neserin; Rippe, Catarina; Swärd, Karl; Albinsson, Sebastian
Abstract : Background: Hypertension remains a major risk factor for cardiovascular diseases, but the underlying mechanisms are not well understood. We hypothesize that appropriate mechanotransduction and contractile function in vascular smooth muscle cells are crucial to maintain vascular wall integrity. The Hippo pathway effectors YAP (yes-associated protein 1) and TAZ (WW domain containing transcription regulator 1) have been identified as mechanosensitive transcriptional coactivators. However, their role in vascular smooth muscle cell mechanotransduction has not been investigated in vivo. Methods: We performed physiological and molecular analyses utilizing an inducible smooth muscle–specific YAP/TAZ knockout mouse model. Results: Arteries lacking YAP/TAZ have reduced agonist-mediated contraction, decreased myogenic response, and attenuated stretch-induced transcriptional regulation of smooth muscle markers. Moreover, in established hypertension, YAP/TAZ knockout results in severe vascular lesions in small mesenteric arteries characterized by neointimal hyperplasia, elastin degradation, and adventitial thickening. Conclusions: This study demonstrates a protective role of YAP/TAZ against hypertensive vasculopathy.